Seismic behavior assessment in vulnerable housing with green roofs: case study in the township of Soacha, Colombia - Ruiz, Daniel; Olaya, Luisa; Rubio, Diego; Torres, Andrés (Revista Ingeniería de Construcción, 2014)
The research group Science and Engineering of Water and the Environment and Social Program of the Faculty of Engineering (PROSOFI) of the Pontificia Universidad Javeriana proposed, for socially vulnerable population, green roofs based on covering the rooftop of houses with potentially productive vegetation. Taking into account that the inertial mass of the green roof could increase the seismic vulnerability of the house, the research group STRUCTURES and CONSTRUCTION performed a seismic structural analysis on the house used as a pilot test for this type of green roofs. A structural dynamic analysis of the building was performed with seismic accelerometers and finite element modeling. Results suggest that the seismic vulnerability of the building was increased by the presence of the green roof as the seismic interstory drift grew 62% and maximum stresses increased by 241%; nevertheless, these increases do not endanger the stability and functionality of the house.